Analisis Fraud Hexagon Terhadap Kecurangan Laporan Keuangan Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2022 - Anggit Lisa Zahara; Dyah Ratnawati (Journal of Economic, Bussines and Accounting (COSTING), 2024)
ABSTRACT This study aims to analyze the effect of the fraud hexagon theory on financial statement fraud as proxied by external pressure, political connection, nature of industry, change in director, change in auditor, and frequent number of CEO's picture in mining companies listed on the Indonesia Stock Exchange (BEI) in 2019-2022. This study used purposive sampling technique so that there were 36 financial reports from 64 companies. The analysis technique and hypothesis testing in this study used PLS (Partial Least Square). The exploration results show that external pressure and nature of industry affect financial statement fraud. While political connection, change in director, change in auditor, and frequent number of CEO's picture have no effect on financial statement fraud. Keywords: Fraud, Financial Statement Fraud, Fraud Hexagon ABSTRAK Penelitian ini bertujuan untuk menganalisis pengaruh dari teori fraud hexagon terhadap kecurangan laporan keuangan yang diproksikan dengan external pressure, political connection, nature of industry, change in director, change in auditor, dan frequent number of CEO’ s picture pada perusahaan pertambangan yang terdaftar di Bursa Efek Indonesia (BEI) tahun 2019-2022. Penelitian ini menggunakan teknik purposive sampling sehingga terdapat 36 laporan keuangan dari 64 perusahaan. Teknik analisis dan uji hipotesis pada penelitian ini menggunaka PLS (Partial Least Square). Hasil eksplorasi menunjukkan bahwa external pressure dan nature of industry berpengaruh terhadap kecurangan laporan keuangan. Sedangkan political connection, change in director, change in auditor, dan frequent number of CEO’s picture tidak berpengaruh terhadap kecurangan laporan keuangan.